Performing Religion in the Stadium: Football and the Dynamics of Interreligious Engagement in Indonesia - Wildan Ulumul Fahmi (Universitas Muhammadiyah Surabaya, 2025)
This article aims to examine the complex relationship between football, public religious expression, social media, and interreligious engagement. The recent phenomenon of a China’s national club goalkeeper which performed like Islamic gesture in the stadium will be the main concern. Using a qualitative case study approach, this article argues that the performed public religious gestures and actions which are amplified in the social media platforms could potentially activate the questions of beliefs and identities. It also could intensify the occurrence of interreligious engagement. The research data are gained from the social media and existing library resources. Analyzing both positive and negative responses towards the contested Islamic gesture phenomenon, this article uses the theory of Public Value as has been grounded by Edoardo Ongaro and the theory of Contact Hypothesis by Gordon Allport. The study finds that the non-religious settings have been neglected in the mainstream discourse of interreligious engagement. It reveals also that the questions of belief become something constant to be asked when the religious gestures or practices are performed publicly in non-religious settings, especially by strangers.